The state and forecast of the system of waste management in Europe and the USA - Biernat, Krzysztof; Dziołak, Paulina Luiza; Samson-Bręk, Izabela (Studia Ecologiae et Bioethicae, 2011)
This article presents waste management in the world and in some highly developed countries in the European Union such as Germany, Netherlands, and Sweden. The article presented also waste management systems in these countries, with special attention to the processes of energy use of waste (Waste to Energy - WTE) in existing plants.